The effects of professional development on science teaching practices and classroom culture - Supovitz, Jonathan A.; Turner, Herbert M. (Journal of research in science teaching, 2000)
The current science education reform movement emphasizes the importance of professional development as a means of improving student science achievement. Reformers have developed a vision for professional development based upon intensive and sustained training around concrete tasks that is focused on subject‐matter knowledge, connected to specific standards for student performance, and embedded in a systemic context. Using data from a National Science Foundation Teacher Enhancement program called the Local Systemic Change initiative, this study employs hierarchical linear modeling to examine the relationship between professional development and the reformers' vision of teaching practice. The findings indicate that the quantity of professional development in which teachers participate is strongly linked with both inquiry‐based teaching practice and investigative classroom culture. At the individual level, teachers' content preparation also has a powerful influence on teaching practice and classroom culture. At the school level, school socioeconomic status was found to influence practice more substantially than either principal supportiveness or available resources. © 2000 John Wiley & Sons, Inc. J Res Sci Teach 37: 963–980, 2000